Female Voice about Love and Affair in Alice Munro’s Stories - Mansurkhodjayeva Madina Toirjon qizi (International Journal on Integrated Education, 2022)
This article describes Alice Munro’s thoughts about the relation between woman and marriage, as reflected in three short stories, 1) “Floating Bridge”, 2) “Nettles”, 3) “What is Remembered”, in short stories collection Hateship, Friendship, Courtship, Loveship, Marriage (2001). In this research, the writer uses feminist theory, namely the gynocriticism proposed by Elaine Showalter. The analysis focuses on the psychoanalytic model to explain the psychology of women who are involved in the marriage but have an affair, as reflected in three main female characters in these stories, they are Jinny, the Narrator, and Meriel. The analysis concludes that, first, the social rules about marriage give a big psychological pressure to the main female characters. Secondly, woman needs an escape for having self-indulgence which, in this case, is the affair that can help them forget the problems temporarily. Thirdly, after getting married, family becomes the most important element in a woman’s life. It is proved by the main female characters stop having an affair because they do not want to destroy their family.